Faktor-Faktor yang Mempengaruhi Adopsi Sistem Pencatatan Panen Berbasis Digital Farming pada Perkebunan Kelapa Sawit di Kebun Bah Birung Ulu - Rifky Fachrezy; Tuty Ningsih (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The application of digital farming in harvest recording management systems is part of a digital transformation aimed at improving the efficiency and accuracy of operational data management in oil palm plantations. The success of adopting such systems is influenced by various factors that need to be analyzed to support optimal technology implementation. This study aims to analyze the influence of technological, human resources (HR), environmental, and management factors on the adoption of digital farming-based harvest recording management systems at Bah Birung Ulu Estate, PT Perkebunan Nusantara IV Regional 2. This study employs a quantitative method with a multiple linear regression approach. The sample was determined using a total sampling technique, consisting of 14 respondents, including estate managers, head assistants, field assistants, harvest foremen, and harvest clerks. Data were collected through questionnaires and analyzed using Statistical Package for the Social Sciences (SPSS) software version 22. The results showed that technological, HR, environmental, and management factors simultaneously had a significant effect on the adoption of digital farming-based harvest recording management systems (p<0.05) with a contribution of 44.3%. Partially, environmental factors had a significant effect on system adoption with a significance value of 0.008 (p<0.05) and became the dominant determinant, whereas technological, HR, and management factors did not show a significant influence (p>0.05). These findings indicate that the successful implementation of digital farming is determined more by the readiness of supporting infrastructure, particularly internet network stability and the accessibility of the work area, rather than internal organizational factors.